The Influence Of Leadership, Motivation And Job Satisfaction On Teacher Performance At SMAN 25 Tangerang Regency - Pujiyanti, Pujiyanti; Mardi Sentosa, Bambang (PT. BATARI EDU CALYA, 2023)
Teachers execute their tasks. The quality of education has not changed, and student scores like the average national exam score remain low, indicating a severe issue. Indonesian education quality issues are shared by all groups. This study used multiple linear regression. Multiple regression has multiple study factors with one dependent variable and multiple independent variables. SMAN 25 Kab. Tangerang must enhance teacher performance by addressing leadership, motivation, and job happiness.